Buhay Ilog integration of informal settlement communities in revitalizing the Pasig Riverfront through low-cost urban collective housing in Barangay Kalawaan, Pasig City - Rosimo, Timothy Bryan T. (College of Architecture, University of the Philippines Diliman, 2025)
The ongoing redevelopment plans for the Pasig River aims to revitalize the use of the waterway by promoting tourism and recreation; however, the plans eye on displacing thousands of informal settler families (ISFs) along the Pasig River to remote areas, threatening their livelihoods and cultivated social linkages. The design advocates for the integration of informal settlers in the revitalization of the Pasig Riverfront due to their decades-long acclimation to the locality and their ingenuity and collective resilience. Consultations with informal settler communities through face-to-face interviews were done to know more about their demands, current situation, and their capacity to take on a proactive approach in addressing urban issues. The community-centric approach in the study dictates the needed spaces and the overall layout of the project. Analysis of the interviews found that most informal settlers along the area have experience with skilled construction, and the social bonds between them and the surrounding community increases their adaptive resilience. The design first aims to address the lack of adequate housing for ISFs to primarily facilitate their proactive capacity in participating in the Pasig Riverfront revival. Prefabricated modular housing construction streamlines the construction process to lessen costs, making housing more affordable to the urban poor. Community spaces and neighborhood amenities were also included to facilitate social linkages and build on their collective resilience. Commercial spaces along the river are also left open for modular and configurable setups, transforming to the ever-changing demands of the community. The design also adapts nature-based solutions to mitigate flood risks associated with the site, and passive regenerative technologies are integrated to develop a low-cost, sustainable structure. The project aims to provide a community-centric framework in approaching future riverfront developments and collective housing projects in the country.